Risk Factors for Stunting Children Aged 6-59 Months In Pulau Panggung District, South Sumatera, Indonesia - Prihatina Anjela; Rachmat Hidayat; Debby Handayanti Harahap (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Background :. Stunting among children is one of the major health problems in developing countries. Globally, 45% of deaths among children are caused by malnutrition, meanwhile stunting, as one of the factors, plays an important role. Children who experience stunting can not achieve optimal growth and cognitive potential. Hence, that will have an impact on future productivity. Muara Enim district is included in one district with stunting prevalence, which is above 20%, i.e. 26.9%. This study was to identify the risk factors of stunting children in Pulau Panggung district, Muara Enim, South Sumatera. Methods: This study applied observational analytic research using cross sectional design. It was conducted on August to October 2017 at public health center in Pulau Panggung district, Muara Enim. There were 83 children who fullfilled the inclusion criteria. The relationship between risk factors and stunting was analyzed using Chi square test and Logistic Regression test was applied to identify the risk factor that play the most role to stunting. Results: 49,4% out of 83 children suffer from stunting, with a mean age of 29,37±13,69 months where the number of children stunting with male gender is 53.7% while female gender is 46.3%. Chi square analysis showed that there was a significant relationship among birth weight, birth length, mother's occupation, history of infection, exclussive breastfeeding and stunting (p< 0.05) but no significant relationship was found among sex, mother's education, maternal height and income with stunting (p> 0.05). Multivariate Logistic Regression test showed that mother's occupation and history of infection are the risk factors that contibute the most to stunting among children aged 6-59 months in Pulau Panggung district. The risk of stunting among working mothers is higher 5 times than unworking mothers and children with infection history have risk of stunting 3 times compared to children without infection history. Conclusion: Mother's occupation and infection history are risk factors that contribute the most to stunting among children at Pulau Panggung district, Muara Enim, South Sumatera.